DIAGNÓSTICO DE SAÚDE DE INDIVÍDUOS ADULTOS DAS FAMÍLIAS DE AGRICULTORES DA REGIÃO NOROESTE DO ESTADO DO RIO GRANDE DO SUL - Cargnin, Deise; Marchi, Dione d.; Franz, Ligia B. B.; Ri, Raquel K. D.; Busnello, Maristela B.; Batistti, Iara; Berlesi, Evelise (Salão do Conhecimento, 2013)
Resumo